2017
DOI: 10.1063/1.4977468
|View full text |Cite
|
Sign up to set email alerts
|

Increasing plasma parameters using sheared flow stabilization of a Z-pinch

Abstract: The ZaP and ZaP-HD Flow Z-pinch experiments at the University of Washington have successfully demonstrated that sheared plasma flows can be used as a stabilization mechanism over a range of parameters that has not previously been accessible to long-lived Z-pinch configurations. The stabilization is effective even when the plasma column is compressed to small radii, producing predicted increases in magnetic field and electron temperature. The flow shear value, extent, and duration are shown to be consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Some notable examples include the current sheet behavior during geomagnetic reconnection [1,2], plasma photonic crystals [3,4], field-reversed configurations (FRC's) [5][6][7], and Z-pinches [8][9][10]. Reddell [2] showed that the distribution plasma function within the thin sheath boundary was not near Maxwellian, but regions inside the reconnected region or far away from the sheath were still near Maxwellian.…”
Section: Introductionmentioning
confidence: 99%
“…Some notable examples include the current sheet behavior during geomagnetic reconnection [1,2], plasma photonic crystals [3,4], field-reversed configurations (FRC's) [5][6][7], and Z-pinches [8][9][10]. Reddell [2] showed that the distribution plasma function within the thin sheath boundary was not near Maxwellian, but regions inside the reconnected region or far away from the sheath were still near Maxwellian.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of sheared flow on current-driven MHD instabilities has previously been investigated theoretically and demonstrated experimentally. [35][36][37][38][39][40][41] Linear MHD calculations show that a sheared axial flow has a stabilizing effect on the kink mode, while a uniform axial flow has no effect on the instability growth. The main prior conclusion is that an axial plasma flow with a linear shear of dV z /dr > 0.1kV A is required for jet stabilization, where k is the axial wave number and V A is the Alfvén velocity.…”
mentioning
confidence: 99%
“…University of Washington/Lawrence Livermore National Lab: Sheared-flow Z-Pinch for Fusion The University of Washington (UW), along with its partner Lawrence Livermore National Laboratory (LLNL), developed a variant of the Z-pinch that exploits sheared flow in the axial direction to mitigate the m=0 and m=1 instabilities that plague Z-pinch plasmas. The concept builds upon prior work in the ZAP and ZAP-HD experiments which demonstrated that a Z-pinch initiated from a high velocity plasma gun experiences a shear flow from r=0 at the center of the Z-pinch axis to r=R at the plasma edge [26], [27] [28]. In those experiments, it was shown that at sufficiently high velocities (typically observed as ~10% of the Alfvén velocity times k, the axial wave number) from the plasma gun, the shear in the plasma was able to suppress the growth of sausage and kink modes in a Z-pinch over a stable period about 700X the expected instability growth time in a non-sheared Z-pinch, at densities of 10 16 -10 17 cm -3 and temperatures of 50-80 eV [27].…”
Section: Integrated Concept Teamsmentioning
confidence: 99%